Pelatihan Pembuatan Hansanitizer Dan Sabun Cuci Dari Herbal Untuk Pencegahan Infeksi Sebagai Upaya Penurunan Stunting Di Desa Pelita Jaya - Mahdalena Sy. Pakaya; Robert Tungadi; Ramly Abudi (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2023)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition so that children are too short for their age. Malnutrition occurs since the baby is in the womb and in the early days after the baby is born, however, stunting only appears after the baby is 2 years old. Data on the prevalence of stunting under five collected by WHO, Indonesia is included in the third country with the highest prevalence in the Southeast Asia region. The average prevalence of stunting under five in Indonesia in 2005 - 2017 was 36.4%. According to the national target, Bone Bolango Regency is one of the 260 Regencies/Cities, priority areas for accelerating the national stunting prevention in 2019. But until now, the prevalence of stunting in Bone Bolango is still high, namely 25.1%, which is above the standard rate. tolerated by WHO, which is below 20%. Based on the results of observations in Pelita Jaya Village, Bone Bolango Regency, cases of stunting that occur are closely related to the lack of availability of clean latrines, where there are still houses that do not have latrines that comply with sanitation requirements. This can trigger cases of infection in children. And if this infection occurs repeatedly, it can cause toddlers and children to experience electrolyte and nutritional deficiencies. So that it can lead to disruption of child development. Based on this, the Service Team, Lecturers of the Faculty of Sports and Health, State University of Gorontalo, need to conduct socialization, training and manufacture of herbal hand sanitizer and hand washing products to improve clean and healthy living behavior in the community, so that they are free from infectious diseases and the risk of stunting.